Ubezpieczenie szpitali - wybrane aspekty finansowe - Rzepecki, Andrzej (Hospital Insurances - Selected Financial Aspects, 2008)
The article presents causes of the increase in insurance premium in hospitals. Moreover, it shows the latest legal regulations connected with insurance. The author also discusses a few preventive methods of activities in order to restrict an increase in insurance premium. The health insurances are described as an additional source of finances for hospitals. Furthermore, the paper presents the important role of an insurance broker in a hospital.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 36, s. 189-194